Insect (Hexapoda) Diversity in the Oceanic Archipelago of Fernando de Noronha, Brazil: Clusiidae (Diptera) - Rafael, José A.; Marques, Dayse W. A.; Limeira-De-Oliveira, F. (Zootaxa, 2023)
For the first time, Clusiidae (Diptera) species are recorded from the oceanic Archipelago Fernando de Noronha, Brazil. They are represented by three genera and seven species: Czernyola fumialula sp. nov., Heteromeringia czernyi Kertész, 1903, Sobarocephala araujoi sp. nov., S. finnilaei Frey, 1918, S. icmbio sp. nov., S. protea Lonsdale & Marshall, 2012, and S. sp. For S. icmbio sp. nov., the aggregation behavior at night was observed on the undersides of broad leaves, females contained an average of 71 eggs, and flight interception traps correlated a positive linear relationship with precipitation seasonally. An illustrated key is presented for all species of the Archipelago.